2018
DOI: 10.1152/ajpgi.00032.2018
|View full text |Cite
|
Sign up to set email alerts
|

Role of mitophagy regulation by ROS in hepatic stellate cells during acute liver failure

Abstract: Liver sinusoids serve as the first line of defense against extrahepatic stimuli from the intestinal tract. Hepatic stellate cells (HSCs) are pericytes residing in the perisinusoidal space that integrate cytokine-mediated inflammatory responses in the sinusoids and relay these signals to the liver parenchyma. Oxidative stress has been shown to promote inflammation during acute liver failure (ALF). Whether and how oxidative stress is involved in HSC inflammation during ALF remains unclear. Level of systemic oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 29 publications
4
29
0
Order By: Relevance
“…Studies have revealed an OS microenvironment in the femoral-head necrotic area in which transplanted BMSCs incur a great deal of stress apoptosis and aging, which seriously limits transplantation effectiveness [11][12][13] . More and more studies have shown that mitochondrial dysfunction and damaged-mitochondria accumulation occur before cell stress apoptosis and senescence [19][20][21][22] . In this study, we preliminarily confirmed that the accumulation of damaged mitochondria was an important cause of BMSCs stress apoptosis and aging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have revealed an OS microenvironment in the femoral-head necrotic area in which transplanted BMSCs incur a great deal of stress apoptosis and aging, which seriously limits transplantation effectiveness [11][12][13] . More and more studies have shown that mitochondrial dysfunction and damaged-mitochondria accumulation occur before cell stress apoptosis and senescence [19][20][21][22] . In this study, we preliminarily confirmed that the accumulation of damaged mitochondria was an important cause of BMSCs stress apoptosis and aging.…”
Section: Discussionmentioning
confidence: 99%
“…Under OS, mitochondria suffer functional damage and accumulate in cells, releasing excessive ROS and apoptosis-inducing factors, which not only oxidatively damage DNA, protein, lipid, and other biological macromolecules, but also activate c-Jun N-terminal kinase (JNK), P38MAPK, DDR, and P53 pathways, ultimately leading to cell stress apoptosis and senescence 21,22,[49][50][51] . Therefore, accumulation of damaged mitochondria is an important cause of stress apoptosis and aging in BMSCs 52 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our recent work showed that during the pathogenesis of ALF, reactive oxygen species activate the NLRP3 inflammasome and promote inflammation in HSCs. We also revealed that LPS treatment induced reactive oxygen species generation in HSCs via mitophagy inhibition[51]. Studies have suggested that in hepatocytes, reactive oxygen species play important roles in the pathophysiology of diseases, including ALF.…”
Section: Liver Failure and Hsc Inflammationmentioning
confidence: 99%